Main indicators of Scots pine (Pinus sylvestris L.) fire resistance within Left-Bank Forest-Steppe - Sydorenko, S. H.; Voron, V. P.; Sydorenko, S. V.; Bolohov, O. M. (Forestry and Forest Melioration, 2019)
Introduction The aim of the study was to determine the basic morphometric indicators of pine fire resistance in typical stands within the Left-Bank Forest-Steppe and their changes with stands aging. Fire resistance determines the degree of a tree’s potential ability to maintain its activity at the individual level after pyrogenic damage. The study of Scots pine fire resistance (Pinus Sylvestris L.) is of great practical importance as such studies serve as a basis for developing of post-pyrogenic mortality models which in turn allow predicting a post-fire viability of damaged trees. The findings on the fire resistance of individual trees will allow in the future developing forest management measures aimed at forming fire resistant pine stands, breeding based on trees fire resistance, etc. Materials and Methods To study morphometric indicators of pine trees resistance to pyrogenic damage, field studies were conducted in the forests within Vasyshchevske Forestry in State Enterprise “Zhovtneve Forest Economy” on 6 study plots. The samples for bark thickness assessment were selected in every other meter of model trees, starting from the ground level, separately in the bark plates and in the cracks. The results were processed by the methods of variation statistics and mathematical-statistical analysis. Results The diameter, height of a tree and height and thickness of its rough bark are the main indicators of a tree’s fire resistance. It was found that the height of the rough bark on the trunk depends on the tree’s diameter (r = 0.95; tf = 11.28; tst0.01 = 3.25) and the age of the trees in the stand (R? = 0.81; r = 0.90; p = 0.05). The height of the rough bark in all age groups was highly variable (V ? 25%). In pine stands, this variability reaches 51%. Based on the obtained results, the statistical-mathematical model was developed which can be used to estimate roughly the height of the rough bark in the stands within Left-Bank Forest-Steppe growing in fresh fairly infertile pine sites (R2 = 0.93; r = 0.97; F = 395.8; Fcrit = 2.6; p = 0.01). The variables in the model are the tree’s diameter and its age. The thickness of the rough bark in the zone where the coarse bark changes to thin bark, in all the cases, ranged from 0.5 to 1.6 mm. In the trees, whose coarse bark goes higher, the thickness of the coarse bark varied within 0.1–0.8 mm in the zone where it changes to thin bark. The bark thickness at a one-meter distance below the zone of transitional bark makes 2–4 mm. Such a bark thickness is not able to prevent the cambium damage caused by fire. Even when the char height on the trunk does not reach the transitional zone where thick coarse bark changes to thin one (1 m below the transitional zone), the risk of damage to the tree tissues increases. Conclusions The height of the rough bark depends mostly on the tree’s diameter and its age. The bark thickness in the near-rootzone of the pine tree trunk is 10–15 times greater than the bark thickness in cracks where it is 1.5–5.8 mm only. During surface fires there is a high risk that the tree cambium will be locally damaged along the cracks. Such damage causes weakening of the tree and along with other unfavorable conditions (drought, stem pests, diseases) leads to its death. 5 Figs., 3 Tables, 15 Refs.